Posttranslational regulation of androgen dependent and independent androgen receptor activities in prostate cancer - Simeng Wen; Yuanjie Niu; Haojie Huang (Asian Journal of Urology)
Prostate cancer (PCa) is the most commonly diagnosed cancer among men in western countries. Androgen receptor (AR) signaling plays key roles in the development of PCa. Androgen deprivation therapy (ADT) remains the standard therapy for advanced PCa. In addition to its ligand androgen, accumulating evidence indicates that posttranscriptional modification is another important mechanism to regulate AR activities during the progression of PCa, especially in castration resistant prostate cancer (CRPC). To date, a number of posttranscriptional modifications of AR have been identified, including phosphorylation (e.g. by CDK1), acetylation (e.g. by p300 and recognized by BRD4), methylation (e.g. by EZH2), ubiquitination (e.g. by SPOP), and SUMOylation (e.g. by PIAS1). These modifications are essential for the maintenance of protein stability, nuclear localization and transcriptional activity of AR. This review summarizes posttranslational modifications that influence androgen-dependent and -independent activities of AR, PCa progression and therapy resistance. We further emphasize that in addition to androgen, posttranslational modification is another important way to regulate AR activity, suggesting that targeting AR posttranslational modifications, such as proteolysis targeting chimeras (PROTACs) of AR, represents a potential and promising alternate for effective treatment of CRPC. Potential areas to be investigated in the future in the field of AR posttranslational modifications are also discussed.